2022
DOI: 10.3390/md20030177
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene and Sorbicillinoid Glycosides from the Endophytic Fungus Trichoderma longibrachiatum EN-586 Derived from the Marine Red Alga Laurencia obtusa

Abstract: An unusual sesquiterpene glycoside trichoacorside A (1) and two novel sorbicillinoid glycosides sorbicillisides A (2) and B (3), together with a known compound sorbicillin (4), were isolated and identified from the culture extract of an endophytic fungus Trichoderma longibrachiatum EN-586, obtained from the marine red alga Laurencia obtusa. Trichoacorside A (1) is the first representative of a glucosamine-coupled acorane-type sesquiterpenoid. Their structures were elucidated based on detailed interpretation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…254 Culture of a Trametes strain yielded spiromeroterpenoids 793 and 794 (ref. 255) and cultures of various Trichoderma strains were the source of trichothecanes 795 – 798 , 256 α-pyrone 799 and decalin 800 , 257 sesquiterpene glycoside 801 and sorbicillinoid glycosides 802 and 803 , 258 β-carboline alkaloids 804 – 807 ( 805 and 806 , known synthetics but new NPs), 259 and polyketides 808 , 809 , 260 810 – 814 . 261 …”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…254 Culture of a Trametes strain yielded spiromeroterpenoids 793 and 794 (ref. 255) and cultures of various Trichoderma strains were the source of trichothecanes 795 – 798 , 256 α-pyrone 799 and decalin 800 , 257 sesquiterpene glycoside 801 and sorbicillinoid glycosides 802 and 803 , 258 β-carboline alkaloids 804 – 807 ( 805 and 806 , known synthetics but new NPs), 259 and polyketides 808 , 809 , 260 810 – 814 . 261 …”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…49 Trichoacorside A (135), isolated from T. longibrachiatum EN-586, was characterized as the first example of a glucosamine-coupled acorane-type sesquiterpenoid, and the bioassay results revealed that compound 135 demonstrated a broad spectrum of antimicrobial activity against methicillinresistant Staphylococcus aureus and the aquatic pathogenic bacterium V. harveyi, as well as multiple plant-pathogenic fungi. 75 The structures of acorane sesquiterpenes 133−135 and the representative bioactive compounds are shown in Figure S6 and Figure 3, respectively. Drimane Sesquiterpenes.…”
Section: Cycloneranementioning
confidence: 99%
“…109 Eight new sorbicillinoids, saturnispols A−H (262−269), were isolated from the endophytic fungus T. saturnisporum DI-IA originating from the marine sponge Dictyonellaincise. 110 A series of new sorbicillinoid derivatives and a new natural compound, including spirosorbicillinol D (294), 2′,3′-dihydroepoxysorbicillinol (295), 113 trichoreesin A (296), 114 2,3dihydro 2-hydroxyvertinolide(297), (−)-trichodermatone (298), 115 and sorbicillisides A (299) and B (300), 75 were discovered from T. longibrachiatum SFC100166, T. reesei Z56-8, Trichoderma sp. FM652 and T. longibrachiatum EN-586, respectively.…”
Section: Cycloneranementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, relatively little is known regarding the nature of biosynthetic gene clusters. Thus, the CRISPR‐Cas system would appear to be an ideal platform for mining novel natural products associated with cryptic and uncharacterized biosynthetic gene clusters from these newly isolated Trichoderma species (Wang et al, 2022 ).…”
Section: Applications Of Crispr‐cas Genome Editing...mentioning
confidence: 99%